Improving transparency and accountability of MSME financial statements by using accrual method - Risnaningsih, Risnaningsih; Tanuwijaya, Sjheny; Iriani, Nur Ida (MEC-J (Management and Economics Journal), 2018)
Many Micro, Small, and Medium Enterprises (MSMEs) are still carrying out a simple accounting record and have not implemented accrual basis method. It is expected that in the future all MSMEs can make more transparency and accountability report by using accrual method so it can assist MSMEs in applying credit to banks or other investors to increase the business capital. This study was conducted in Malang Regency, Batu City, and Malang City. This study used descriptive qualitative method. The data collection techniques were done by interview and documentation with sampling technique using purposive sampling and snowball sampling. The collected data will be analyzed by interactive analysis method including data reduction, data presentation, and data verification or interpretation. The results showed that the owners of SMEs in managing their finances use simple accounting by using accrual method so that the financial statements produced more accurate than if the owners of MSMEs use cash method. The owners of SMEs do not need to make complete financial statements, they may use three types of financial statements, namely: income statement, balance sheet, and cash flow statement. The income statement is used to find out how much the profit or loss of the MSMEs, the balance sheet is used to find out the assets, liabilities, equity, and cash flow statement is used to find out the changes occurring during the period of operating, investing, and financing activities. These three types of financial statements have already been used by MSME owners as one of the requirements to obtain credit from banks or other investors.